Emerging respiratory infections threatening public health in the Asia‐Pacific region: A position paper of the Asian Pacific Society of Respirology1. Issue 6 (15th April 2019) - Park, Sunghoon; Park, Ji Young; Song, Yuanlin; How, Soon Hin; Jung, Ki‐Suck; ,
ABSTRACT: In past decades, we have seen several epidemics of respiratory infections from newly emerging viruses, most of which originated in animals. These emerging infections, including severe acute respiratory syndrome coronavirus (SARS‐CoV), Middle East respiratory syndrome coronavirus (MERS‐CoV) and the pandemic influenza A(H1N1) and avian influenza (AI) viruses, have seriously threatened global health and the economy. In particular, MERS‐CoV and AI A(H7N9) are still causing infections in several areas, and some clustering of cases of A(H5N1) and A(H7N9) may imply future possible pandemics. Additionally, given the inappropriate use of antibiotics and international travel, the spread of carbapenem‐resistant Gram‐negative bacteria is also a significant concern. These infections with epidemic or pandemic potential present a persistent threat to public health and a huge burden on healthcare services in the Asia‐Pacific region. Therefore, to enable efficient infection prevention and control, more effective international surveillance and collaboration systems, in the context of the 'One Health' approach, are necessary.